Temporal dynamics of the ABC transporter response to insecticide treatment: insights from the malaria vector Anopheles stephensi - Epis, Sara (Sci Rep, 2014)
In insects, ABC transporters have been shown to contribute to defence/resistance to insecticides by reducing toxic concentrations in cells/tissues. Despite the extensive studies about this detoxifying mechanism, the temporal patterns of ABC transporter activation have been poorly investigated. Using the malaria vector Anopheles stephensi as a study system, we investigated the expression profile of ABC genes belonging to different subfamilies in permethrin-treated larvae at different time points (30 min to 48 h). Our results showed that the expression of ABCB and ABCG subfamily genes was upregulated at 1 h after treatment, with the highest expression observed at 6 h. Therefore, future investigations on the temporal dynamics of ABC gene expression will allow a better implementation of insecticide treatment regimens, including the use of specific inhibitors of ABC efflux pumps.